Wednesday

November 26, 2014

November 26, 2014

Posted by **help shaikha 3** on Tuesday, August 28, 2012 at 2:04pm.

(a) x3 + 6x2 – 11x + 6

(b) x3 – 6x2 + 11x – 6 *

(c) x3 + 6x2 + 11x + 6

(d) x3 – 6x2 – 11x – 6

how ?

- math -
**Steve**, Tuesday, August 28, 2012 at 3:02pmif the roots are 1,2,3, then

(x-1)(x-2)(x-3) = 0

expand to get (b)

By the way, none of the answers as written are equations. the correct answer would be

x^3 - 6x^2 + 11x - 6 = 0

**Answer this Question**

**Related Questions**

math - I solved this problem 12x-6=11x -6+6=0 11x+6 12x=11x+6 12x-11x=x 11x-11x=...

ap algebra - Please help me with this problem. I dont know what to do. Use the ...

algebra - find a third degree polynomial equation with coefficients that has ...

Math: Please check my answers - 1. What is the degree of the monomial 3x2y3? 2 3...

algebra - 1)Solve by factoring:5x^2=4-19x answer=-4,1/5 2)Which quadratic ...

math - what is the equation of a line that passes through (1,-4) and (2,7)? a. y...

Math - Can anyone help work these problumns out step by step? 11x-37=x+23 10p-26...

math - show that 3/2 and 1/3 are roots of the quadratic function y=6x2(squared...

math - find the sum and product of the roots of the equation 5x^2+11x-3=0 ?

algebra PLZ HELP!!! - y= 9/11x-17 9x-10y=179 You need to use parentheses to tell...